Big Ideas in Public Relations Research and Practice - Frandsen, Finn; Johansen, Winni; Tench, Ralph; Romenti, Stefania (Advances in public relations and communication management, 2019)
Drawing on contributions from the 2018 congress of the European Public Relations Education and Research Association (EUPRERA), this volume explores and analyses challenges around communication, management and big ideas to present findings from current research in corporate communication.